Evaluation of undergraduate psychiatry teaching in Malawi - Amy E. Lindsay; Stephen Byers (BJPsych International, 2015)
In Malawi, mental health services account for only 2% of the health budget; there are just 4.5 full-time psychiatrists and 433 psychiatric beds. The Scotland Malawi Mental Health Education Project (SMMHEP) aims to provide sustainable support for psychiatric training for healthcare professionals and has increased the number of psychiatrists in the country. There has been a recent change in the educational programme in order to maximise clinical exposure and experience, particularly with the care of in-patients. The new programme has had a positive effect on students' attitudes towards psychiatry and their consideration of psychiatry as a career. This paper supports the ongoing work SMMHEP does in developing psychiatric services through education.